(untitled) (Biological Sciences - PJSIR, 1995)
Scaling up of the mushroom culti vation from 1.5 kg rice straw/tray to 18 kg/tower (120 cm long, 70 cm diameter) and double layer spawning method improved the yield of the crop by 4 -5%. Tower system has two fold advantages a no wood is required for making the trays and shelves, thus reducing the cost. Secondly, the yield was more (5 %) than tray system as the system provides a long verticle sides all around the bed for fruitification.